Alterations in Cytosolic and Mitochondrial [U-13C]Glucose Metabolism in a Chronic Epilepsy Mouse Model - Tanya S. McDonald; Catalina Carrasco‐Pozo; Mark P. Hodson; Karin Borges (2017)
Temporal lobe epilepsy is a common form of adult epilepsy and shows high resistance to treatment. Increasing evidence has suggested that metabolic dysfunction contributes to the development of seizures, with previous studies indicating impairments in brain glucose metabolism. Here we aim to elucidate which pathways involved in glucose metabolism are impaired, by tracing the hippocampal metabolism of injected [U-13C]glucose (i.p.) during the chronic stage of the pilocarpine-status epilepticus mouse model of epilepsy. The enrichment of 13C in the intermediates of glycolysis and the TCA cycle were quantified in hippocampal extracts using liquid chromatography-tandem mass spectroscopy, along with the measurement of the activities of enzymes in each pathway. We show that there is reduced incorporation of 13C in the intermediates of glycolysis, with the percentage enrichment of all downstream intermediates being highly correlated with those of glucose 6-phosphate. Furthermore, the activities of all enzymes in this pathway including hexokinase and phosphofructokinase were unaltered, suggesting that glucose uptake is reduced in this model without further impairments in glycolysis itself. The key findings were 33% and 55% losses in the activities of pyruvate dehydrogenase and 2-oxoglutarate dehydrogenase, respectively, along with reduced 13C enrichment in TCA cycle intermediates. This lower 13C enrichment is best explained in part by the reduced enrichment in glycolytic intermediates, whereas the reduction of key TCA cycle enzyme activity indicates that TCA cycling is also impaired in the hippocampal formation. Together, these data suggest that multitarget approaches may be necessary to restore metabolism in the epileptic brain.